2015
DOI: 10.1039/c5ra05732a
|View full text |Cite
|
Sign up to set email alerts
|

Highly monodisperse magnetite/carbon composite microspheres with a mesoporous structure as high-performance lithium-ion battery anodes

Abstract: In this study, we propose a fabrication method for highly monodisperse magnetite/carbon (Fe3O4/C) composite microspheres with a mesoporous structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…‡ 6,[8][9][10][11][12][13][14][15] However, Fe 2 O 3 -based anodes suffer from pulverization and electrode cracking caused by large volume change ($200%) upon repetitive cycling reactions between Fe 2 O 3 and Li ions. [16][17][18][19][20][21][22][23] The low coulombic efficiency for the 1st cycle and the high polarization also limit Fe 2 O 3 as the anode material for LIBs. 24 To overcome these obstacles, Fe 2 O 3 nanostructures such as nanoparticles, 25 nanocubes, 26 nanorods, 27 nanoakes 28 and nanotubes 17 have been synthesized for LIBs in the initial stage, because these nanostructures could shorten the diffusion distances for Li + ions, [29][30][31] which can reduce polarization to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…‡ 6,[8][9][10][11][12][13][14][15] However, Fe 2 O 3 -based anodes suffer from pulverization and electrode cracking caused by large volume change ($200%) upon repetitive cycling reactions between Fe 2 O 3 and Li ions. [16][17][18][19][20][21][22][23] The low coulombic efficiency for the 1st cycle and the high polarization also limit Fe 2 O 3 as the anode material for LIBs. 24 To overcome these obstacles, Fe 2 O 3 nanostructures such as nanoparticles, 25 nanocubes, 26 nanorods, 27 nanoakes 28 and nanotubes 17 have been synthesized for LIBs in the initial stage, because these nanostructures could shorten the diffusion distances for Li + ions, [29][30][31] which can reduce polarization to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the preparation of Fe 3 O 4 /C composites with fine nanostructure by the specific reaction between Fe 3þ and polymer carbon sources has attracted much attention. [34][35][36][37] For example, alginate can cross-link with polyvalent metal ions to form gels. [38,39] After drying and carbonization, the gels can turn into metal oxides/carbon with nano-sized particles.…”
mentioning
confidence: 99%
“…8,14,17,18 Notably, it has been shown that Fe 3 O 4 octahedra yielded a higher cycling performance as compared with that of cubes and cuboctahedra, thereby highlighting the importance of the exposed surface in dictating the observed electrochemical properties of as-prepared magnetite nanomaterials. 8 In essence, our overall strategy has been to fabricate consistent, standardized series of monodisperse motifs of colloidal magnetite nanocrystals [17][18][19][20][21][22][23][24][25][26][27][28] by carefully tuning size, shape, and chemical composition through meticulous parameter selection. 29 In so doing, we have concentrated on exploring the electrochemical activity of well-defined 0D and 2D structures of magnetite.…”
mentioning
confidence: 99%